A Comparative Study of Financial Ratios of Automotive Industry: A Cross Country Analysis - Behcet, Fahriye (Eastern Mediterranean University - Doğu Akdeniz Üniversitesi, 2019)
Consequential percentage in economy of many countries are supported by value adding production systems of automobile companies. Automotive sector creates high rivalry among the countries. Strength of the sector in each country is determined by the total average achievement of all companies. Financial ratios are used to measure liquidity, efficiency, solvency and profitability of companies. In this study, return on equity ratio, return on asset ratio, profit margin ratio, gross profit ratio, EBIT ratio, EBITDA ratio, asset turnover ratio, stock turnover ratio, current ratio, liquidity ratio, solvency ratio, and gearing ratio have been used for analysis. Comparison among France, Germany, Italy, Japan, Korea, Spain and Turkey for period 2008 to 2016 has been covered by descriptive statistics, ANOVA test and representation of nine year trend. Results represents that; Italian automotive industry has extreme financial fluctuations. In contrast, France, Germany and Spain has common and more stable general trend. Far East countries; Japan and Korea, have independent ratio averages. Turkey has completely independent, increasing trend compare to industry averages of other countries. In addition, Turkey has highest profitability average according to descriptive statistic results. Keywords: Financial analysis, Automotive industry, Financial ratios.

ÖZ:Otomotiv endüstrisi birçok ülke ekonomisi üzerinde önemli rol oynamaktadır. Otomotiv firmalarının ülke ekonomisine kattığı önemli değer, ülkeler arası ekonomik rekabeti de arttırmaktadır. Finansal rasyolar, şirketlerin likidite, karlılık, finansal yapı ve faaliyet oranlarını ölçmek amacıyla kullanılmaktadır. Bu çalışmada seçilen on iki farklı finansal rasyo, Fransa, Almanya, Italya, Japonya, Kore, İspanya ve Türkiyede’ki otomotiv endüstrisinin finansal yapısını karşılaştırmak amacıyla kullanılmıştır.Her bir finansal rasyo için, 2008 – 2016 yılları arasında, ülke bazında elde edilen toplam statistikler; temel statistik oranları, ANOVA testi ve dokuz yıllık sürecin trend analizi kullanılarak kıyaslanmıştır. Yapılan analizler doğrultusunda; Italyan otomotiv endüstrisinde büyük oranda finansal dalgalanmalar olduğu görülmüştür. Bunun yanında, Fransa, Almanya ve İspanyadaki otomotiv endüstrilerinin genellikle ortak ve İtalya’ya oranla daha dengeli bir finansal yapısı olduğu saptanmıştır. Avrupa ülkelerinin gösterdiği uyumlu hareketlerin aksine, Uzakdoğu ülkelerindeki finansal rasyo ortalamalarında hiç bir ortak eğilime rastlanmamıştır. Türkiye, diğer ülkelerden bağımsız olarak artan ivmeye sahip olup, genel ortalamalarda daha yüksek karlılık göstermektedir. Anahtar Kelimeler: Finansal analiz, Otomotiv endüstrisi, Finansal rasyolar.
Master of Business Administration. Institute of Graduate Studies and Research. Thesis (M.B.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Co-Supervisor: Asst. Prof. Dr. Hasan Özyapıcı and Supervisor: Assoc. Prof. Dr. İlhan Dalcı.
Keywords: Business Administration; Automobile industry and trade-Finance; Financial analysis; Automotive industry; Financial ratios